Evaluation Revealing Errors: A Study of Cross-Divisional Cost Recording Systems in Multi-Batch Projects at PT X - Hakim, Muhammad Irham; Kartini, Kartini (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to evaluate cross-divisional cost recording systems in a multi-batch project at PT X by examining recording failures as a structural and systemic organizational phenomenon. A descriptive qualitative approach with a single case study design was employed. The units of analysis included the Finance Division as the guardian of data integrity, the Product Division as the producer of cost data, and the CEO as the strategic decision-maker. Data were collected through semi-structured interviews, internal documents, and project records, and analyzed using triangulation. The findings indicate that cost recording problems cannot be interpreted merely as technical errors but rather as consequences of a recording and control system design that is misaligned with the characteristics of batch-based projects. Misalignment between the Cost of Goods Sold (COGS) and the Budget Plan weakened the linkage between planning and realization, resulting in reactive cost control. Evaluation conducted after Batch 2 led to improvements in Batch 3, where increased detail and separation of fixed and variable costs enhanced cost accuracy, although systematic evaluation mechanisms remained limited.